Defining lower airway bacterial infection in children with chronic endobronchial disorders. Issue 2 (19th December 2017) - Hare, Kim M.; Pizzutto, Susan J.; Chang, Anne B.; Smith‐Vaughan, Heidi C.; McCallum, Gabrielle B.; Beissbarth, Jemima; Versteegh, Lesley; Grimwood, Keith
Abstract: Background: Differentiating lower airway bacterial infection from possible upper airway contamination in children with endobronchial disorders undergoing bronchoalveolar lavage (BAL) is important for guiding management. A diagnostic bacterial load threshold based on inflammatory markers has been determined to differentiate infection from upper airway contamination in infants with cystic fibrosis, but not for children with protracted bacterial bronchitis (PBB), chronic suppurative lung disease (CSLD), or bronchiectasis. Methods: BAL samples from children undergoing bronchoscopy underwent quantitative bacterial culture, cytologic examination, and respiratory virus testing; a subset also had interleukin‐8 examined. Geometric means (GMs) of total cell counts (TCCs) and neutrophil counts were plotted by respiratory pathogen bacterial load. Logistic regression determined associations between age, sex, Indigenous status, antibiotic exposure, virus detection and bacterial load, and elevated TCCs (>400 × 10 3 cells/mL) and airway neutrophilia (neutrophils >15% BAL leukocytes). Results: From 2007 to 2016, 655 children with PBB, CSLD, or bronchiectasis were enrolled. In univariate analyses, Indigenous status and bacterial load ≥10 5 colony‐forming units (CFU)/mL were positively associated with high TCCs. Viruses and bacterial load ≥10 4 CFU/mL were positively associated with neutrophilia; negative associations were seen for Indigenous status and macrolides. In children who had not received macrolide antibiotics, bacterial load was positively associated in multivariable analyses with high TCCs at ≥10 4 CFU/mL and with neutrophilia at ≥10 5 CFU/mL; GMs of TCCs and neutrophil counts were significantly elevated at 10 4 and 10 5 CFU/mL compared to negative cultures. Conclusions: Our findings support a BAL threshold ≥10 4 CFU/mL to define lower airway infection in children with chronic endobronchial disorders.